SIMULATION AND CONTROL OF FEED CONDITIONING SYSTEM FOR SGS TECHNOLOGY/OFFSHORE FACILITIES - OTHMAN, NURZATIL AQMAR (2019)
The main advantage of SGS technology in comparison to other conventional CO2separation technologies is the glaring difference in terms of its size, weight and footprint. The technology is highly efficient if the feed conditions are maintained at its desired specifications. However, the lack of internal rotating parts results in the inability to efficiently control its operation. Hence, designing a proper control strategy for the feed conditioning plant of SGS is highly crucial. In this study three control strategies were developed using PID controllers to handle the process disturbances ;i.e. pressure, temperature, and CO2composition,as these parameters greatly influences the CO2separation efficiency in Twister.